DARI SEJARAH LOKAL SUL-SEL KE SEJARAH LOKAL SUL-SELBAR: MEMIKIRKAN PERSPEKTIF BARU SEJARAH LOKAL - Burhaman Burhaman (Fakultas Ilmu Budaya universitas Hasanuddin, 2019)
The main question being raised in this paper is what is local history? Does local history stand by itself or is it part of the national history? What is the different between local history with, say, national history? Does local history have its own theory, concept and methodology which are different that other histories? These questions have more meaning if thet are related to what Taufik Abdulah (1985) and Sarono Kartodirdjo (1993) said that local history is not a local version of national history and national history is not the sum of local histories. Local history and national history are intertwined but each has its own methodology, concept and scope that are different with others‟. This paper elucidates these issues using south Sulawesi histories. Keywords: historiography, local history, south Sulawesi.